KARAKTERISTIK KEKERASAN SEKSUAL TERHADAP ANAK PEREMPUAN DI WONOGIRI DAN BOYOLALI - Suwandi, Joko; Chusniatun, Chusniatun; Kuswardani, Kuswardani (Jurnal Pendidikan Ilmu Sosial, 2019)
The future of this nation depends on the quality of its young generation. Sexual violence against daughters that is rampant today can damage the growth of the spiritual and physical body of the young generation. For this reason, a preventive solution is needed for prevention. This initial study will identify the characteristics of sexual violence against girls which occur in two regions, namely Wonogiri and Boyolali. This research was the qualitative descriptive analytic study that explored and described the characteristics of sexual violence against girls in the two regions. Data was collected through in-depth interviews and document review of key informants, PPA Polres officers, Head of P2TP3A, Head of Women and Children Protection, Solopos.com news and Kompasanda.com, and other key informants. Data were analysed using GAP techniques to obtain insightful initial data. The research conclusion is as follows. a) Most intrafamilial abuses are carried out by stepfather, biological father, victim's sibling and grandfather. b) Extrafamilial violence abuse is carried out by the same age victim’s friends and playing that mocking the victims in abuzz and begin with alcoholic parties. The perpetrator with the status of a boyfriend is difficult to trace, and the actual cases are very large in number. c) Institutional violence abuse often occurs in elementary and junior high schools with the perpetrators is a teacher. The victims are more than one student. d) Ritualistic abuse takes the form of shamanic practices. The triggers are such as; a) inharmonious family situation, b) unfavourable economic conditions, c) unhealthy social environment, d) the negative influence of social media use, e) unstable psychological conditions, and f) superficial understanding of religion